1952
DOI: 10.1002/zaac.19522680406
|View full text |Cite
|
Sign up to set email alerts
|

Über eine Hilfsapparatur zur Messung der Lichtbrechung von hygroskopischen Pulvern

Abstract: Professor Franx Hein xum 60. Geburtstag gewidmet InhaltsubersichtEr wird eine Einbettungskamrner mit Stromungsvorrichtung beschrieben, rnit deren Hilfe die Lichtbrechung auch von hygroskopischen durchsichtigen Pulvern nach der BEcKEschen Methode unter dem Polarisationsinikroskop bestimmt werden kann.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 0 publications
1
32
0
Order By: Relevance
“…5 reveal a shift of the main peak, but none of the curves possess a prepeak as frequently observed for phosphate glasses [42]. Reverse Monte Carlo simulations on the basis of diffraction data with high real-space resolution have shown [15] that the main peak of the SðsÞ function of the Zn metaphosphate sample mainly originates from the superposition of the Zn 2þ -PO 4 phosphate glass systems, a prepeak could be expected to be produced by the Zn 2þ -PO 4 -Zn 2þ correlations. For example, the pronounced prepeak observed in the SðsÞ function of La metaphosphate glass is mainly attributable to the La 3þ -PO 4 -La 3þ correlations [43].…”
Section: Short-range and Intermediate-range Structurementioning
confidence: 85%
See 2 more Smart Citations
“…5 reveal a shift of the main peak, but none of the curves possess a prepeak as frequently observed for phosphate glasses [42]. Reverse Monte Carlo simulations on the basis of diffraction data with high real-space resolution have shown [15] that the main peak of the SðsÞ function of the Zn metaphosphate sample mainly originates from the superposition of the Zn 2þ -PO 4 phosphate glass systems, a prepeak could be expected to be produced by the Zn 2þ -PO 4 -Zn 2þ correlations. For example, the pronounced prepeak observed in the SðsÞ function of La metaphosphate glass is mainly attributable to the La 3þ -PO 4 -La 3þ correlations [43].…”
Section: Short-range and Intermediate-range Structurementioning
confidence: 85%
“…Attributable to the unusual discontinuities in the composition-property dependence, Kordes et al [4] identified the zinc and magnesium phosphate system as Ôanomalous'. This unusual behavior was originally explained [4] by a coordination change of the Zn 2þ or Mg 2þ cation, respectively, from 4 to 6 at metaphosphate composition, but there was no experimental support for this explanation. As just shown, the Zn-O coordination number is invariant across the entire polyphosphate concentration range.…”
Section: Short-range and Intermediate-range Structurementioning
confidence: 98%
See 1 more Smart Citation
“…Magnesium phosphate glasses exhibit unusual properties and were classified as 'anomalous phosphate glasses' by Kodrdes et al 1)3) The anomalous properties of magnesium phosphate glasses are attributed to the variation of the MgO coordination number from 6 to 4. 1) Many researchers have focused on MgO P 2 O 5 binary glasses and discussed their structures.…”
Section: Introductionmentioning
confidence: 99%
“…1) Many researchers have focused on MgO P 2 O 5 binary glasses and discussed their structures. 4)13) Magnesium in phosphate glasses acts as a network modifier and/or former depending on their composition, i.e., intermediate oxides: the role is determined by the phosphate chain length.…”
Section: Introductionmentioning
confidence: 99%